Analysis of exchange rates in the economic uncertainty era - Salim, Tiara; Soelistyo, Aris (Optimum: Jurnal Ekonomi dan Pembangunan, 2024)
The exchange rate, an essential macroeconomic indicator, reflects the economy's strength. In 2023, global economic uncertainty poses a risk to the health of a country's economy, particularly impacting the exchange rate, which is crucial for global economic transactions. This study examines how exports, inflation, interest rates, GDP, and a dummy variable for economic uncertainty affect the rupiah's value against the USD. The study employs the Error Correction Model (ECM) and tests based on classical assumptions to conduct this analysis. Understanding the indicators that influence fluctuations in the rupiah exchange rate is critical in planning effective economic policies, so this research is essential to provide in-depth insight into how short-term and long-term influences on the exchange rate are affected by independent variables as well as contributing to the understanding of policy in predict exchange rates. This research concludes that exports, inflation, and GDP are the factors that dominate this research in designing policies to maintain the stability of the Rupiah currency against the USD in facing the threat of economic uncertainty. The implication of the study that government needs to strengthen exports and maintain the stability of price to control inflation.